Lanthanum Carbonate - A New Phosphate Binding Drug in Advanced Renal Failure - Aaseth, Jan; Bjorke-Monsen, Anne-Lise (Current Medicinal Chemistry, 2018)
Background: Lanthanum (La) is considered to be a non-essential element. La has been used for several decades in China to improve yield in plant production and has also been shown to have significant performance enhancing effects in feeding trials on animal husbandry. The estimated dietary intake of La in humans is below 150 μg, which is lower than 10% of the estimated limit of safe and acceptable daily intake. Methods: The present review is based on literature search in available databases. Results: Upon ingestion of La as carbonate, the lanthanum ion (La3+) is released in the stomach and traps dietary phosphate as insoluble lanthanum phosphate complexes in the gut, thereby inhibiting phosphate absorption. Lanthanum carbonate as a drug to lower serum phosphate in endstage kidney failure was approved for human use by the US FDA in 2004 and by the EU in 2006. When used to treat patients with advanced renal insufficiency, lanthanum carbonate is administered orally at a dose of maximally 3000 mg per day. The uptake of lanthanum ions from the gut to the circulation is negligible. And few systemic side effects have been recorded upon the use of lanthanum carbonate as a phosphate binding drug, although gastrointestinal discomfort with pain, vomiting and diarrhea may occur. Lanthanum carbonate has the potential to chelate to drugs with anionic groups and therapeutic co-administration with lanthanum carbonate may reduce the bioavailibility of drugs like tetracyclines, quinolones and levothyroxine. Conclusion: The findings in this review confirm that lanthanum carbonate is a clinically useful phosphate binding drug with few side effects in advanced renal failure.
Keywords: hyperparathyroidism